Optimum selection of information terminals for production monitoring in manufacturing industries - Kleindienst, Jani (Strojniški vestnik, 2008)
The purpose of automated acquisition of production data in manufacturing industries is aimed to provide accurate data about the performance of the scheduled tasks and the production process. Hence, easier and more effective production control can be achieved. The information acquired includes the duration of each operation, the number of manufactured items of products, the amount of scrap as well as the duration of downtimes and their root-causes. A way to acquire relevant data makes use of special-purpose information terminals. The problem that arises here is how to select the optimum number ofthe terminals in order to minimize the overall losses. The approach presented below relies on optimization of a stochastic criterion function, which combines the terminal costs and costs related to the waiting times during busy sessions. The solution suggested is based on using the distribution of events, recorded during the past production session. A case study dealing with optimum selection of terminals in a real production processis presented in detail.
Keywords: organizacija proizvodnje; proizvodni sistemi; terminali; optimiranje; nadzor; krmiljenje